PENCIPTAAN CUSTOMER VALUE DI MASON PINE HOTEL MELALUI DISTINCTIVE CAPABILITIES (Survei Pada Tamu yang Menginap di Mason Pine Hotel) - Sari, Anggi Puspita (2014)
Today, increasing growth of the hospitality that's not comparable with the development occupancy resulting higher competition inside the hotel industry. Of necessity and desire that is changing every time require the company to undertake a strategy to provide more value than competitors. Kotler & Keller (2012:33) explains that in today's competition, buyers are faced with a variety of options, the company can only win the competition if it is able to deliver more value to its customers. According to Cravens and Nigel F. Piercy, (2013:9) "one way to provide customer value by using distinctive capabilities. Where is the distinctive capabilities can make a company has a competitive advantage, difficult to imitate and can be used in a competitive situation. In accordance with that disclosed by Selznick (1957) in Kim Man (2009:21) that "distinctive capabilities as a source of competitive advantage". This research aims to obtain findings on the effect of distinctive capabilities towards the creation of customer value. The object is Mason Pine Hotel. The independent variable in this research is a distinctive capabilities (X) with the dependent variable is the customer value (Y). The type of this research is descriptive and verification and cross section method development methods with systematic random sampling. Is an analytical technique used path analysis with SPSS 20 obtained R-Square of 45%. And the remaining 55% is influenced customer value by another factors not examined in this research. Based on the results of research through path analysis a significant difference either simultaneously or partially from the dimensions of reputation and innovation in creating a customer value consisting of product benefit/cost, service benefit/cost, personnel benefit/cost and image benefit/cost. The author recommends to the presence of deeper assessment on the distinctive capabilities or use other variables that can create a customer value. Keyword : Distinctive Capabilities, Customer Value, Mason Pine Hotel Dewasa ini meningkatnya pertumbuhan perhotelan yang tidak sebanding dengan perkembangan tingkat hunian mengakibatkan tingginya persaingan di dalam industri perhotelan. Adanya kebutuhan dan keinginan yang terus mengalami perubahan setiap waktunya menuntut perusahaan untuk melakukan strategi dengan memberikan nilai yang lebih dibandingkan pesaing. Kotler & Keller (2012:33) menjelaskan bahwa dalam persaingan saat ini pembeli dihadapi dengan berbagai pilihan, perusahaan hanya dapat memenangkan persaingan tersebut jika mampu memberikan nilai yang lebih terhadap pelanggannya. Menurut Cravens & Nigel F. Piercy, (2013:9) "Salah satu cara yang dapat memberikan customer value dengan menggunakan distinctive capabilities" Dimana Distinctive capabilities tersebut dapat membuat perusahaan memiliki keunggulan dalam bersaing, sulit untuk ditiru dan dapat digunakan dalam beberapa situasi persaingan. Sesuai dengan yang diungkapkan oleh Selznick (1957) dalam Kim Man (2009:21) bahwa "distinctive capabilities as a source of competitive advantage". Penelitian ini bertujuan untuk memperoleh temuan mengenai pengaruh strategi distinctive capabilities terhadap penciptaan customer value. Objek penelitian ini yakni Mason Pine Hotel. Variabel bebas dalam penelitian ini adalah distinctive capabilities (X) dengan variabel terikat yaitu customer value (Y). Adapun jenis penelitian ini adalah deskriptif dan verifikatif dan metode pengembangan cross section method dengan teknik sampling systematic random sampling. Teknik analisa yang digunakan adalah path analysis dengan bantuan program SPSS 20 didapat R-Square sebesar 45%. Dan sisanya yakni 55% dipengaruhi oleh adanya faktor pembentuk customer value lainnya yang tidak diteliti dalam penelitian ini. Berdasarkan hasil penelitian melalui analisis jalur terdapat pengaruh yang signifikan baik secara simultan maupun parsial dari dimensi reputation dan innovation dalam menciptakan customer value yang terdiri dari product benefit/cost, service benefit/cost, personnel benefit/cost dan image benefit/cost. Penulis merekomendasikan untuk adanya pengkajian lebih dalam lagi mengenai strategi distinctive capabilities ini atau menggunakan variabel lain yang dapat menciptakan customer value. Kata Kunci : Distinctive Capabilities, Customer Value, Mason Pine Hotel